Molecular Marker Applications in Oat (Avena Sativa L.) Breeding and Germplasm Diagnostics - Benazir Katarina, Marquez (Université d'Ottawa / University of Ottawa, 2014)
The ability to identify germplasm and select traits accurately is fundamental to successful plant breeding. Pedigrees and molecular markers facilitate these processes; however misleading experimental results can occur when incorrect relationships and/or cultivar names are recorded. Molecular markers can identify these inconsistencies, and with advances in genotyping technology these diagnostics can be done faster and more objectively. This study aimed to develop molecular marker assays and graphical genotyping methodologies for cultivar identification, seed purity assessment and trait selection in oat (Avena sativa L.). KBioscience’s Allele-Specific PCR (KASP™) and genotyping-by-sequencing (GBS) technologies were applied to a set of current Canadian oat cultivars to evaluate their utility for identifying cultivars and detecting intra-cultivar variation. Both KASP™ and GBS detected different extents of heterogeneity among a set of 160 seeds that originated from four seed sources of four cultivars. In both cases, the detected variation did not appear to be limited to a specific cultivar or seed source, reinforcing that all cultivars are heterogeneous. Graphical genotyping localized heterogeneity to specific chromosome regions, thereby distinguishing physical contamination from true genetic heterogeneity and heterozygosity. Pre-existing genotype data for 700 oat cultivars and breeding lines were also used to construct graphical genotypes for pedigree validation and discovery of potential sources for favourable quantitative trait loci (QTL) alleles. This methodology used historical QTLs and anchoring markers to identify 25 putative “high oil” allele carriers. The results from this study will provide diagnostic tools for cultivar identification and pedigree validation, in addition to meaningful information about existing heterogeneity and possible QTL locations in current cultivars.
Keywords: oat (Avena sativa L.); DNA fingerprinting; genotyping-by-sequencing (GBS); graphical genotyping; single nucleotide polymorphism (SNP); quantitative trait loci (QTL); pedigree; haplotype; intra-cultivar variation; cultivar; genomic heterogeneity; KBioscience's Allele-Specific PCR (KASP)